Nursing students' knowledge and attitudes regarding brominated flame retardants from three Croatian universities - Krešimir Jakšić; Marijana Matek Sarić; Jelena Čulin (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study explored Croatian nursing students' knowledge and attitudes regarding brominated flame retardants (BFRs) as indicators of their predisposition to educate future patients. The purpose of the study was to identify knowledge gaps and barriers and to propose possible remedies. Design/methodology/approach - The cross-sectional survey was conducted on a convenience sample of 114 nursing students at undergraduate and graduate levels from three Croatian universities during the winter semester in the academic year 2018-2019. Descriptive and inferential statistical analyses were performed using STATISTICA 13 software. Findings - Slightly over half of the students (58.49%) were knowledgeable of BFR health effects and 45.28% showed knowledge about its presence in the environment. Only 33.02% of students identified prenatal exposure effects and 24.53% answered correctly about legislative actions. Participants expressed modest interest in the topic (M = 3.15, SD = 1.35). Although informing the public on the health consequences of BFRs was important to them (M = 4.18, SD = 1.03), they did not perceive health-care providers as primarily responsible for communicating that information. Originality/value - There is a need to enhance related content in the curriculum to improve students' knowledge. Raising students' awareness regarding the role of nurses in clinical and policy arenas is proposed to facilitate active participation in improving environmental health.